Abraham Lincoln and Liberal Democracy. - Buccola, Nicholas (University Press of Kansas, 2016)
An ideologically and methodologically diverse group of scholars reflect on the nature and significance of Abraham Lincoln's political thought. Although viewing Lincoln from different perspectives and through different lenses, the contributors to this volume coalesce around the idea that Lincoln's political thought has enduring relevance for how we think about liberal democracy.